Women and education. The case of the Vedrunas in the Basque Country, Nineteenth and Twentieth Century - Berdote Alonso, Esther (Historia y Memoria de la Educación, 2016)
The social representation of a woman as a wife and mother in the nineteenth century determined her lack of instruction and, therefore, high rates of illiteracy among women. Despite clear legislative support, scarcity of state economic sources to support the education of girls in the nineteenth century made their access to schools difficult. This reality, coupled with other circumstances, laid the foundation for new religious teaching congregations dedicated to women’s education. This paper analyses the model of education for women provided by the Carmelite Sisters of Charity from the time of their arrival to the Basque Country (1870) until the beginning of the Second Republic (1931). The analysis focuses on three elements: the process of the new foundations, pedagogical and curricular organization of the schools, and incorporation of the Basque language into the educational process. In order to analyse the model, the researcher has consulted as a primary source the Statutes of each school, which belonged to the provincial archive of the Congregation. The research carried out suggests that the Carmelite Sisters of Charity demonstrated a high degree of adaptability to the local village communities by offering the Basque lessons in certain schools while also maintaining their core mission of Christianising and educating girls.